Application of cooperative learning modules with the Jigsaw-type to volleyball learning outcomes - Nurmayasari, Dinda; Pradana, Febryansah Gilang Aris; Adila, Fekie; Juniarisca, Dwi Lorry; Hidayat, Taufiq (Universitas Negeri Surabaya, 2024)
The development of learning outcomes in physical education for students in the 21st century depends on innovation and a series of learning models designed by educators to improve children's critical thinking skills. In the jigsaw cooperative learning model with the advantage of a deeper understanding of the material, cooperation between students is formed, students' motivation in sports increases, and students are trained in responsibility. For junior high school students, there is volleyball material which is one of the big ball game materials. This research aims to find out whether the application of the jigsaw type cooperative learning model can improve volleyball learning outcomes for junior high school level students. This investigation uses quantitative research with a pure experimental type through a randomized control group pretest-posttest design. In this study, the instruments used were knowledge tests and skills tests, with samples using cluster random sampling to determine 2 classes, namely 8-D as the experimental class and 8-C as the control class. The results of this study used parametric tests on knowledge tests with P-value results of 0.00 < 0.05, which means there was an increase in learning outcomes using the jigsaw-type cooperative learning model on student knowledge and on skills tests with non-parametric tests with results obtained p < 0.05, which means there was significant improvement. Student learning outcomes increased by 68.27% on the knowledge test and by 68.27% on the skills test using the N-Gain test. So it can be concluded that the application of the jigsaw cooperative influences volleyball learning outcomes in the improvement category quite effectively.